THE MEANING OF NEWS VALUES FOR CONTENT CREATORS ON THE SNACK VIDEO PLATFORM - Batubara, Denny Setiawan; Fotaleno, Fahmy (jfpublisher, 2023)
The issue of news values is a great concern in news content spreading on social media platforms. One of the social media platforms that encourages content creators to create news content is the Snack Video platform. The management of Snack Video’s platform enforces strict rules that must be adhered to by all its users to ensure that all content created by content creators has news value. This qualitative research aims to identify the interpretations of these news value rules by using Shannon and Weaver’s message transmission model. This research is using literature as a data collection technique while applying the phenomenological method to explain how audio-visual content is used to disseminate information through social media. The findings of the research identified that the use of regulations conveyed by the transmission of this message is proven to increase the quality of news content in Snack Video through the meaning of all content creators towards the rules established by Snack Video management. The Snack Video management also found to have made several special requirements for each news content which would be checked manually by the agency team using quality parameters that have been determined in detail.